2013
DOI: 10.1007/s10456-013-9371-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human lymphatic malformation endothelial cells, their in vitro characterization and in vivo survival in a mouse xenograft model

Abstract: Human lymphatic vascular malformations (LMs), also known as cystic hygromas or lymphangioma, consist of multiple lymphatic endothelial cell-lined lymph-containing cysts. No animal model of this disease exists. To develop a mouse xenograft model of human LM, CD34(Neg)CD31(Pos) LM lymphatic endothelial cells (LM-LEC) were isolated from surgical specimens and compared to foreskin CD34(Neg)CD31(Pos) lymphatic endothelial cells (LECs). Cells were implanted into a mouse tissue engineering model for 1, 2 and 4 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 50 publications
2
35
0
1
Order By: Relevance
“…However, we have found that the LM LECs proliferate faster and are more resistant to apoptosis than foreskin LECs 15 suggesting that there is a primary defect in the LM LECs. When LM LECs are implanted in a mouse xenograft model, they form structures reminiscent of lymphatic malformations 15 . This supports a hypothesis that lymphatic malformations may be caused by one or more somatic mutations arising in LM LECs during fetal development.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…However, we have found that the LM LECs proliferate faster and are more resistant to apoptosis than foreskin LECs 15 suggesting that there is a primary defect in the LM LECs. When LM LECs are implanted in a mouse xenograft model, they form structures reminiscent of lymphatic malformations 15 . This supports a hypothesis that lymphatic malformations may be caused by one or more somatic mutations arising in LM LECs during fetal development.…”
mentioning
confidence: 72%
“…Kaposiform lymphangiomatosis is an example of an LEC tumor 14 . Lymphatic malformations are thought to arise during embryonic development and grow in proportion to the child 15,16 . They rarely regress but can remain asymptomatic until trauma or infection precipitates rapid growth leading to clinical complications.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations